Pérdida dental y su relación con la calidad de higiene oral en los y las estudiantes de la Universidad Nacional de Loja de la modalidad de estudio presencial en el periodo mayo-julio de 2014 - Ramos Vicente, Jorge Luis (2014)
The research was performed on tooth loss and its relation to the quality of oral hygiene in the students of the National University of Loja in the form of classroom study belonging to the period May -July 2014” The objectives namely the frequency of tooth loss, the parts most affected, and the frequency of oral hygiene methods student at UNL. At the National University of Loja students presented a considerable loss of teeth (1081), a frequency of students who did not lose teeth was (55%), while (45%) has some tooth loss, quality Regular hygiene (53%), brushing frequency (53.35%), the use of dental floss in a (29%), mouthwash (33%) and (38.92%) visit the dentist twice . The ratio of tooth loss and quality of oral hygiene was found, the level Well the (IHO-S) there was (352) individuals representing (40%) of which the frequency of tooth loss is (105) teeth and percentage (10%). in contrast those who had a regular level (OHI-S) were (477) persons representing (53%) of which the frequency of tooth loss is (410) pieces representing (38%). those who had a level bad (OHI-S) had a frequency of 65 individuals representing 7% of which had a frequency of loss representing 566 parts (52%). Keywords: Tooth Loss, Quality of oral hygiene (OHI), Oral hygiene methods.